Synthesis on Heavy Higgs from the Standard Model to 2HDM and Beyond - Abdeljalil Habjia, (JOURNAL OF ADVANCES IN PHYSICS, 2020)
In the context of particle physics, within the ATLAS and CMS experiments at large hadron collider (LHC), this work presents the discussion of the discovery of a particle compatible with the Higgs boson by the combination of several decay channels, with a mass of the order of 125.5 GeV. With increased statistics, that is the full set of data collected by the ATLAS and CMS experiments at LHC ( s1/2 = 7GeV and s1/2 = 8GeV ), the particle is also discovered individually in the channel h-->γγ with an observed significance of 5.2σ and 4.7σ, respectively. The analysis dedicated to the measurement of the mass mh and signal strength μ which is defined as the ratio of σ(pp --> h) X Br(h-->X) normalized to its Standard Model where X = WW*; ZZ*; γγ ; gg; ff. The combined results in h-->γγ channel gave the measurements: mh = 125:36 ± 0:37Gev, (μ = 1:17 ± 0:3) and the constraint on the width Γ(h) of the Higgs decay of 4.07 MeV at 95%CL. The spin study rejects the hypothesis of spin 2 at 99 %CL. The odd parity (spin parity 0- state) is excluded at more than 98%CL. Within the theoretical and experimental uncertainties accessible at the time of the analysis, all results: channels showing the excess with respect to the background-only hypothesis, measured mass and signal strength, couplings, quantum numbers (JPC), production modes, total and differential cross-sections, are compatible with the Standard Model Higgs boson at 95%CL. Although the Standard Model is one of the theories that have experienced the greatest number of successes to date, it is imperfect. The inability of this model to describe certain phenomena seems to suggest that it is only an approximation of a more general theory. Models beyond the Standard Model, such as 2HDM, MSSM or NMSSM, can compensate some of its limitations and postulate the existence of additional Higgs bosons.